Exploring Environmental Disclosure in Selected Australian Multinationals under the GRI Guidelines (Issues in Social and Environmental Accounting (ISEA), 2014)
This paper explores changes in environmental reporting among Australian MNEs between 2004 and 2007, using the GRI guidelines, and explains how GRI transformation (from G2 to G3) leads to changes in environmental disclosure aspects along with their association with company size, profitability, industry sector. Applying Wilcoxon matched pair signed ranked and Spearman rank correlation tests, twenty companies from the Australian SAM Sustainability Index (AuSSI) are examined to identify the extent of changes on specific aspects of environ mental disclosure. The findings of the paper document a significant increase in environmental reporting in Australian companies. In particular, reporting has increased for energy, emissions and environmental management followed by water, overall, materials, transport and product/ services aspects. However, a shift in emphasis from compliance and biodiversity aspects asso ciated with climate changes and resource preservation is also evident. Again, the majority of changes occurred in companies operating in environmentally sensitive industries with industry sector having significant relationship with a few environmental disclosure aspects, the study shows no significant effect of company size and profitability on different environmental disclo sure aspects. These evidences indicate that external forces (such as, legislation, industry sensi tiveness to environment, and stakeholder awareness and pressure) rather than internal factors are more effective to influence and determine environmental disclosure in Australian compa nies